Las Relaciones Internacionales en Rusia: desarrollo de la disciplina y política exterior - Quiñones de la Iglesia, Francisco Javier (Journal of the Spanish Institute for Strategic Studies, 2025)
International Relations (IR) emerged as an academic discipline at the end of World War II, linked to the newly acquired American hegemony, which facilitated the consolidation of the realist paradigm of the discipline. At the same time, the development of IR in the Soviet Union was conditioned by the official Marxist ideology that reduced approaches to the strategic interests of the state. Finally, when Soviet IR specialists were able to access Western literature, they understood that their approaches could be compared to those of structural realism in capitalist thought. This work studies the state of the art of the discipline in Russia, from the Soviet period to the present and the transfer of theory to foreign policy. It concludes that the absolute predominance of the realist approach in Russia responds to the fact that it is the only one that can provide an appropriate theoretical framework for practical issues of foreign policy, among which the national interest stands out.
Keywords: Structure; power; foreign policy; international relations; international system